汽车主动悬架模糊PID控制器的设计 - 续海峰; 张慧鹏 (Jixie chuandong)
A 2-degree-of-freedoms （2 DOF） model of the automotive active suspension is built,and the new strategy combining the fuzzy control theory and PID control theory is employed to control the active suspension system. The control system is numerically simulated in Mat lab and Semolina. The simulation results show that the active suspension is superior to the passive suspension in improving the ride comfort ability,and the active suspension Fuzzy-PID control based on fuzzy theory is applicable and remarkably effective.